Electrical and optical simulation of nPERT solar cells with epitaxially grown emitters. (September 2017) - Filipič, Miha; Payo, Maria Recaman; Bearda, Twan; Depauw, Valerie; Radhakrishnan, Hariharsudan Sivaramakrishnan; Van Nieuwenhuysen, Kris; Filipek, Izabela Kuzma; Duerinckx, Filip; Debucquoy, Maarten; Gordon, Ivan; Szlufcik, Jozef; Poortmans, Jef
Abstract: One of the advantages of an epitaxially grown emitter is that its doping profile is not limited by the diffusion process and that almost any arbitrary profile shape can be realized. In this simulation study we make use of the epitaxial doping profile's flexibility to optimize the emitter of an nPERT solar cell. Initially an optical and electrical model is set up in Sentaurus TCAD and calibrated based on measurements of an actual device with an efficiency of 22.5%. Next, simulations for a box shaped profile with varying thicknesses and doping concentrations are carried out. Additionally, a two-step emitter consisting of a combination of two box profiles – one located at the surface and another deep profile underneath the former one – is also simulated. The results clearly identify the optimal doping concentrations and thicknesses which result in the highest efficiencies. Outside of these optimal regions the most significant loss mechanisms are pointed out. To be highlighted is that the switch from a the single box profile emitter to an optimal two-step profile emitter realizes a gain of 0.4% absolute resulting in an efficiency of 22.9%. This demonstrates that the freedom in the shape of the epitaxial doping profile can be employed to further increase the solar cell efficiencies.